Audiological biomarkers of tinnitus in an older Portuguese population - Haider, Haúla F.; Ribeiro, Diogo; Ribeiro, Sara F.; Trigueiros, Nuno; Caria, Helena; Borrego, Luís; Pinto, Iola; Papoila, Ana L.; Hoare, Derek J.; Paço, João (Frontiers in Aging Neuroscience, 2022)
Tinnitus is a phantom sound perceived in the absence of external acoustic stimulation. It is described in a variety of ways (e.g., buzzing, ringing, roaring) and can be a single sound or a combination of different sounds. Our study evaluated associations between audiological parameters and the presence or severity of tinnitus, to inform tinnitus diagnosis, treatment, and prognosis. Our sample included 122 older participants (63 women, 59 men), aged 55 to 75 years from the Portuguese population, with or without sensory presbycusis and/or tinnitus. All participants underwent a clinical evaluation through a structured interview, Ear, Nose, and Throat observation, and audiological evaluation (standard and extended audiometry, psychoacoustic tinnitus evaluation, auditory brainstem responses, and distortion product otoacoustic emissions). The Tinnitus Handicap Inventory was used to measure tinnitus-symptom severity. Our data confirm that the odds of developing tinnitus were significantly higher in the presence of noise exposure and hearing loss. Also, both participants who had abrupt tinnitus onset and moderate or severe sensitivity to sound featured higher odds of moderate, severe, or catastrophic tinnitus. However, it was in the ABR that we obtained the most exciting and promising results, namely in wave I, which was the common denominator in all findings. The increase in wave I amplitude is a protective factor to the odds of having tinnitus. Concerning the severity of tinnitus, the logistic regression model showed that for each unit of increase in the mean ratio V/I of ABR, the likelihood of having moderate, severe, or catastrophic tinnitus was 10% higher. Advancing knowledge concerning potential tinnitus audiological biomarkers can be crucial for tinnitus adequate diagnosis and treatment.